Comparative sensitivity and inhibitor tolerance of GlobalFiler® PCR Amplification and Investigator® 24plex QS kits for challenging samples. (May 2018) - Elwick, Kyleen; Mayes, Carrie; Hughes-Stamm, Sheree
Highlights: The tolerance to common PCR inhibitors and sensitivity of two megaplex STR kits was evaluated. GlobalFiler® may display a higher sensitivity. The Investigator® 24plex QS kit may be more tolerant to PCR inhibitors. Average peak heights appear to be larger with the GlobalFiler® kit. Abstract: In cases such as mass disasters or missing persons, human remains are challenging to identify as they may be fragmented, burnt, been buried, decomposed, and/or contain inhibitory substances. This study compares the performance of a relatively new STR kit in the US market (Investigator® 24plex QS kit; Qiagen) with the GlobalFiler® PCR Amplification kit (Thermo Fisher Scientific) when genotyping highly inhibited and low level DNA samples. In this study, DNA samples ranging from 1 ng to 7.8 pg were amplified to define the sensitivity of two systems. In addition, DNA (1 ng and 0.1 ng input amounts) was spiked with various concentrations of five inhibitors common to human remains (humic acid, melanin, hematin, collagen, calcium). Furthermore, bone (N = 5) and tissue samples from decomposed human remains (N = 6) were used as mock casework samples for comparative analysis with both STR kits. The data suggest that the GlobalFiler® kit may be slightly more sensitive than the Investigator® kit. On average STR profiles appeared to be more balanced and average peak heights were higher when using the GlobalFiler® kit. However, the data also show that the Investigator® kit may be more tolerant to common PCR inhibitors. While both STR kits showed a decrease in alleles as the inhibitor concentration increased, more complete profiles were obtained when the Investigator® kit was used. Of the 11 bone and decomposed tissue samples tested, 8 resulted in more complete and balanced STR profiles when amplified with the GlobalFiler® kit.